Programa de intervención en funciones cvognitivas para estudiantes universitarios consumidores de tabaco (2024)
The study conducted at the Antonio Nariño University, Ibagué campus, employed a quasiexperimental pretest-posttest approach involving 10 university students aged 20 to 24. The aim was to measure whether there was a change in initial cognitive functions (memory, attention, and inhibition) after the program implementation. To achieve this, the ASSIST screening, Wechsler Memory Scale-IV, d2 attention test, and Stroop color-word test were administered. Inclusion and exclusion criteria ensured sample homogeneity. The "Training for Cognitive Functions R&P" program was expected to meet project objectives. Following implementation, significant progress was noted in the evaluated abilities, indicating noticeable improvement in participants' capacity to perform stimulation exercises more quickly and effectively.Keywords: Cognitive functions (CF), memory, attention, inhibition, tobacco, nicotine, processes, program, stimulation, students, smokers.